Single-Layer 79 GHz Microstrip Patch Array for All-Weather Automotive Radar (Journal of Modern Mechanical Engineering and Technology, 2025)
Advanced driver-assistance systems (ADAS) demand radar sensors that combine centimetre-level resolution, wide angular coverage, and all-weather reliability, yet must fit behind a plastic bumper at automotive cost. This study meets that challenge with a fully self-contained 79 GHz front-end fabricated on a single-layer RO3003 printed-circuit board.Closed-form cavity models, applied from first principles, yield patch dimensions without iterative tuning. Sixteen patches arranged in a 4 × 4 half-wavelength array deliver 16 dBi broadside gain, 3.2 GHz (−10 dB) impedance bandwidth, and a 33° half-power beam-width, thereby covering the entire 76–81 GHz allocation.Solving the radar-range equation shows that even under 8 dB km⁻¹ heavy-rain attenuation the sedan detection limit contracts by only 2 m (51 m → 49 m), while motorcycle and pedestrian ranges are virtually unaffected. To our knowledge, this is the first single-layer PCB radar front-end to achieve such performance without empirical tuning, and it offers a clear upgrade path toward imaging radar and highway ACC.